ANALISIS PEMBAGIAN TUGAS DAN KEWENANGAN ANTARA BUPATI DAN WAKIL BUPATI KUANTAN SINGINGI PERIODE 2016-2021 DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Dolla Feradila; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The phenomenon of open disharmony between the Regional Head and Deputy RegionalHead often occurs, one of which occurs in the Regent and Deputy Regent of Kuantan SingingiRegency for the 2016-2021 period. In this case, the Deputy Regent felt he was not involved inmaking some policies. Therefore, the purpose of this thesis research is, firstly, the pattern ofdivision of tasks and authorities between the Regent and Deputy Regent in the perspective ofLaw no. 23 of 2014 concerning Regional Government in Kuantan Singingi Regency for the2016-2021 period. Second, the ideal concept of the division of tasks and authority between theRegent and Deputy Regent in administering government in the region, especially in KuantanSingingi Regency.This type of research can be classified into the type of sociological juridical research.With the research location in Kuantan Singingi Regency. While the population and sampleare parties related to the problem under study. This study uses primary and secondary datasources and data collection techniques are carried out by means of interviews and literaturereview.From the results of the research problem there are two main things that can beconcluded. First, the pattern of division of tasks and authority between Regent Mursini andDeputy Regent Halim in Kuantan Singingi Regency for the 2016-2021 period was not carriedout properly due to disharmony between the two caused by unclear division of tasks andauthorities; not so good communication; and it is not further elaborated in the Regent'sProvisions. Second, the ideal concept of division of tasks and authorities between the Regentand Deputy Regent in administering local government must refer to the provisions of theapplicable laws as the principle of legality; the creation of intensive communication; issuanceof a decision in accordance with the Regional Government Law as a juridical instrument forthe division of tasks between the Regent and Deputy Regent; and good governance must becreated. The author's suggestion is that first changes to the Regional Government Law.Second, ideally the division of tasks and authorities between the Regent and the DeputyRegent must: understand and carry out their duties and authorities by referring to theprovisions of the applicable laws as the principle of legality; create intensive communication;issue a decision in accordance with the Regional Government Law as a juridical instrumentfor the division of tasks between the Regent and Deputy Regent; and must create goodgovernance; and the existence of fair budget arrangements.